Historicum Calamitatum (Masa-masa Kekalutan) Dunia Islam dalam Historiografi Ibn Athīr di dalam al-Kāmil - Koes Adiwijayanto (Qurthuba: The Journal of History and Islamic Civilization, 2017)
This article is on historiographical analysis about how Ibn Athīr, one of outstanding classical Muslim historians at Memlukites era, explored his sources and contemporary documents to construct his Kāmil fī Tārīkh. As an eyewitness to the chronological events before his subtle eyes, this article tries to value him as an historiogrpher and his remarkable works, to cover up the decline of Ummah during the second period of AbbƗsid era. When the loyalty of devoted believers are divided in the Jum„a attributed to the different pretenders of khilƗfah title, in the same times the dissolutions of its unity became the major problem between Muslims from multiple ethnics, race, sects, blood and stains. The clashes and perpetual conflicts for predominant control over nostra mare Mediterranean Sea between Muslims and Christian kingdoms too had contribution on shaping Muslim position how to react to their lost in the southern part of Iberian Peninsula and islands over the Mediteranean.